Olivia plans a tea party - Shaw, Natalie; Spaziante, Patrick (New York, N.Y. : Simon Spotlight, 2011)
"Olivia the assistant party planner has a very important party to plan...a tea party! With the help of Francine, Olivia throws a tea party unlike any other!"--p. [4] of cover.
"Based on the TV series Olivia as seen on Nickelodeon."-- p. [4] of cover.
Cover title.
Keywords: Olivia (Fictitious character : Falconer) -- Juvenile fiction; Afternoon teas -- Juvenile fiction; Parties -- Juvenile fiction